2007
DOI: 10.1007/s10705-006-9070-6
|View full text |Cite
|
Sign up to set email alerts
|

Crop residue, manure and fertilizer in dryland maize under reduced tillage in northern China: II nutrient balances and soil fertility

Abstract: A long-term experiment was carried out in the dryland of northern China to assess the effects of applications of maize stover, cattle manure and NP (1:0.44) fertilizer on partial nitrogen (N), phosphorus (P) and potassium (K) balances, extractable soil N (SEN), P and K, and soil organic matter (SOM) in a spring maize cropping system, under reduced tillage conditions. The experiment was set-up according to an incomplete, optimal design, with three factors at five levels and 12 treatments, including a control wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…This design has proven to be efficient for experiments with nutrient inputs. However, nutrient management under rainfed conditions requires rainfall to be taken into account in a dynamic approach (see also Wang et al 2007) to explain the strong interactions between GSR and the effects of NP fertilizer, stover and manure. The feasibility and adoptability by farmers of split applications of N fertilizer combined with soil and/or plant analyses should be tested in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This design has proven to be efficient for experiments with nutrient inputs. However, nutrient management under rainfed conditions requires rainfall to be taken into account in a dynamic approach (see also Wang et al 2007) to explain the strong interactions between GSR and the effects of NP fertilizer, stover and manure. The feasibility and adoptability by farmers of split applications of N fertilizer combined with soil and/or plant analyses should be tested in practice.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore assessed the long-term effects of these applications on maize grain yield and nutrient use efficiency. A companion paper (Wang et al 2007) describes the effects of these combined applications on N, P and K balances, soil organic matter dynamics and soil fertility indices.…”
Section: Introductionmentioning
confidence: 99%
“…Current fertilizer N application rates of 550-600 kg N per hectare annually in Taihu region of east China and on the North China Plain could be cut by 30-60% while still maintaining crop yields and N balance in the rotation and substantially reducing N losses to the environment (Ju et al 2009). Compared to N, application of K has been neglected in many developing countries including Asian countries and this has resulted in the continual depletion of soil K (Regmi et al 2002;Panaullah et al 2006;Ladha et al 2003;Wang et al 2007b;Lal et al 2007). Frequent K deficiency has been observed in crops in these regions (Dobermann et al 1996;Panaullah et al 2006;Mussgnug et al 2006).…”
mentioning
confidence: 99%
“…But at three sites (B6, B8 and C7), yield was greater with ammonium nitrate, while at two sites (B9 and C13) yield was greater with application of urea. Wang et al (2007) earlier reported that understanding concepts of ideal soil fertility level and response to nutrient management provide practical guidelines for improving nutrient management under the variable rainfall conditions. While, Okalebo et al (2006) suggested that site specific recommendations are needed for maize because of its differential response to nutrient inputs which varied widely within and across agro-ecological zones.…”
Section: Year Effectsmentioning
confidence: 99%